الوسطية والاعتدال في الخطاب الديني واثره على تربية الفرد والمجتمع - الانسي, عبد السلام حمود غالب (Proceeding of International Conference on Islamic Education (ICIED), 2022)
Religious speech is one of the most important types of mutual speeches among people, building convictions, due to its impact on its recipients, its role in establishing principles, and the consequent change in ideas, beliefs and habits, as well as being one of the tributaries of continuing education, in terms of its distinct nature; It is a cognitive discourse that affects thought and treats behavior, and it is directed to multiple age groups, and in light of the information and technology revolution, it spreads very quickly and ideas and principles spread. Their upbringing is an adult and beneficial education, and this can only be achieved through a moderate and moderate religious speech, far from convulsions, excluding the other and not accepting the one who opposes him in the doctrine or idea. Man is born on innocence, common sense and harmony, and then the family interferes in the formation of his personality, and that is the moderate and moderate religious discourse. There is no doubt that it has an impact on the education of the individual and society and the building of the Muslim’s relationship with the others; In terms of acceptance or rejection, and this must have an impact on achieving a decent life and peaceful coexistence in society, accepting the other and spreading harmony and harmony. This research shows the concept of moderation and as well as education and the characteristics of the desired religious speech and contributing to the education of the individual and society with mentioning the impact of this woodcutter in Education and upbringing of the individual and society using the inductive method as well as the descriptive analytical method.